2018
DOI: 10.1063/1.5026831
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-type defects in Al2O3/GaN structure probed by monoenergetic positron beams

Abstract: Defects in the Al 2 O 3 (25 nm)/GaN structure were probed by using monoenergetic positron beams. Al 2 O 3 films were deposited on GaN by atomic layer deposition at 300 C. Temperature treatment above 800 C leads to the introduction of vacancy-type defects in GaN due to outdiffusion of atoms from GaN into Al 2 O 3. The width of the damaged region was determined to be 40-50 nm from the Al 2 O 3 /GaN interface, and some of the vacancies were identified to act as electron trapping centers. In the Al 2 O 3 film befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Positron annihilation spectroscopy is a nondestructive method with selective sensitivity to neutral and negative vacancy-type defects, and second-order sensitivity to negatively charged defects without open volume [11]. Thanks to these properties, positron annihilation methods have been successful in identifying the role of native point defects in the electrical compensation of n-type doped compound semiconductors such as GaN, ZnO, AlN, InN, and In 2 O 3 [12][13][14][15][16], as well as their alloys such as InGaN and AlGaN [17][18][19][20][21][22]. In spite of the otherwise significant research interest in β-Ga 2 O 3 , the number of reported studies with positron annihilation is surprisingly low [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Positron annihilation spectroscopy is a nondestructive method with selective sensitivity to neutral and negative vacancy-type defects, and second-order sensitivity to negatively charged defects without open volume [11]. Thanks to these properties, positron annihilation methods have been successful in identifying the role of native point defects in the electrical compensation of n-type doped compound semiconductors such as GaN, ZnO, AlN, InN, and In 2 O 3 [12][13][14][15][16], as well as their alloys such as InGaN and AlGaN [17][18][19][20][21][22]. In spite of the otherwise significant research interest in β-Ga 2 O 3 , the number of reported studies with positron annihilation is surprisingly low [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…After the deposition, they were annealed at temperatures ranging (227) up to 900 • C for 3-5 min in N 2 atmosphere. Details on the deposition conditions of the Al 2 O 3 and AlON x films are given elsewhere [5,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…Measured annihilation parameters are clearly different from the reference values thus indicating presence of defects. An increase in the S parameter typically indicates increase in vacancy-type defect concentration or increase in vacancy volume [140][141][142]. However, the shape of the (S, W) plot for the undoped and highly Si-doped sample ([Si] = 9 × 10 18 cm −3 ) in Fig.…”
Section: Trap States At Algan/gan Interface Of N-polar Hemtsmentioning
confidence: 98%